2022
DOI: 10.1101/2022.03.02.482703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focal adhesion-based cell migration is differentially regulated in vivo versus in vitro by Paxillin phosphorylation

Abstract: SummaryFocal adhesions are important subcellular structures that physically link the cell to the extracellular matrix (ECM), thus facilitating efficient cell migration. Although in vitro cell culture studies have provided a wealth of information regarding focal adhesion biology, it is critical to understand how focal adhesions are dynamically regulated in their native environment. We developed a zebrafish transplantation system in which we could efficiently visualize focal adhesion structures during single cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…These punctae formed at cell protrusion sites and dispersed when the protrusions retracted ( Barros-Becker et al, 2017 ). Work from our own lab using the same-species transplantation of highly migratory zebrafish melanoma cells expressing fluorescently labeled Paxillin showed that Paxillin co-localizes with actin to form dynamic focal adhesion structures at sites of cell-ECM contact during single cell migration ( Xue et al, 2022 ). Taken together, these studies suggest that focal adhesion structures form during in vivo single cell migration.…”
Section: In Vivo Analysis Of Focal Adhesionsmentioning
confidence: 99%
“…These punctae formed at cell protrusion sites and dispersed when the protrusions retracted ( Barros-Becker et al, 2017 ). Work from our own lab using the same-species transplantation of highly migratory zebrafish melanoma cells expressing fluorescently labeled Paxillin showed that Paxillin co-localizes with actin to form dynamic focal adhesion structures at sites of cell-ECM contact during single cell migration ( Xue et al, 2022 ). Taken together, these studies suggest that focal adhesion structures form during in vivo single cell migration.…”
Section: In Vivo Analysis Of Focal Adhesionsmentioning
confidence: 99%